Growth of Shorea stenopthera Burck. F. seed on Application Composting Litter Shorea sp. and Fungi Scleroderma columnare on Latosol Soil PERTUMBUHAN BIBIT Shorea stenopthera BURCK. F. TERHADAP APLIKASI KOMPOS SERASAH Shorea sp. DAN FUNGI Scleroderma column - Mohamad Saefudin; Basuki Wasis; Erdy Santoso (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
Growth of Shorea stenopthera Burck. F. seed can naturally be associated with fungi Scleroderma columnare. A fall composting litter can accumulate on the floor of forest naturally, litter piles thickness affect the presence of fungi Scleroderma columnare that situated in the field around the trees rooting of Shorea stenopthera Burck. F. This research aims to examined the role of Scleroderma columnare fungi inoculation and the addition of litter against the growth of seedlings of Shorea stenopthera Burck. F. The treatments are designed using two factorials of completely randomized design for compost and fungi Scleroderma columnare. Compost factor consist of three levels, without compost, pure compost, and chopped compost. Fungi factor consist of two levels, with addition and without addition of Scleroderma columnare. The treatments repetition is 30 times, and observation data is analyzed by Duncan test (with 95% of confidence level), and test of variance for studying the interaction among diverse treatments. The results of the analysis gives significant difference between sample with treatment and sample without treatment (A0B0). Treatment A1B0 (chopped compost; without scleroderma) has the best response to the height of tree, trunk diameter, weight of wet leaf, and weight of stalks. Treatment A2B1 (pure compost; Scleroderma) showed the significant influence to the sum of wet trunks and percentage of colony. Treatment A0B1 (without compost; Scleroderma columnare) showed the significant difference on weight total of root against any other treatments.Key words : fungi Scleroderma columnare, litter, Shorea stenopthera Burck. F.